(untitled) (Training and Practice : Journal of Educational Sciences, 2016)
As a result of the cooperation between the University of Szeged, Institute of Kindergarten and Lower-Primary and the Qualitas T&G Kft., within the framework of TÁMOP 4.1.2.B.2-13 / 1-2013-0008 Mentor(h)áló 2.0 project, individual development of students was carried out. Altogether 18 students of the Institute took part in the program. Our aim was to help these students to realize those skills and areas of their personality which should be developed. This study aims at presenting the process of creating the program for individual skills development. All of the students volunteered for this program and their anonimity was assured. The structure of the development and the documentation was the same for everyone. Measuring the students’ behavioral competences (RaDAr) provided the input of the process (Barath, 2013). Tailor-made techniques and practices provided the basis of the mentoring process.